2014
DOI: 10.1371/journal.pone.0088328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Immunogenic Proteins from Mycoplasma bovis and Establishment of an Indirect ELISA Based on Recombinant E1 Beta Subunit of the Pyruvate Dehydrogenase Complex

Abstract: The pathogen Mycoplasma bovis (M. bovis) is a major cause of respiratory disease, mastitis, and arthritis in cattle. Screening the key immunogenic proteins and updating rapid diagnostic techniques are necessary to the prevention and control of M. bovis infection. In this study, 19 highly immunogenic proteins from M. bovis strain PD were identified using 2-dimensional gel electrophoresis, immunoblotting and MALDI-TOF/TOF MS. Of these 19 proteins, pyruvate dehydrogenase E1 component beta subunit (PDHB) showed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 33 publications
(47 reference statements)
3
64
1
Order By: Relevance
“…Other proteins are rarely described as surface displayed. Antibodies specific to PdhA, PdhB, and PdhC were detected in sera of animals infected with M. bovis (45). PdhB was shown to be surface localized in Lactobacillus plantarum and interacts with human fibronectin (46).…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins are rarely described as surface displayed. Antibodies specific to PdhA, PdhB, and PdhC were detected in sera of animals infected with M. bovis (45). PdhB was shown to be surface localized in Lactobacillus plantarum and interacts with human fibronectin (46).…”
Section: Discussionmentioning
confidence: 99%
“…They include exposed surface proteins, such as variable surface proteins (Vsp), the lipoproteins P26, P48-like, and mycoplasma immunogenic lipase A (MilA), and the immunodominant membrane protein pMB67 [12, 13, 14, 15, 16, 17], as well as cytoplasmic proteins, such as heat-shock protein 60 (Hsp60), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and the pyruvate dehydrogenase beta (PDHB) subunit, among others [18, 19, 20]. The highly-conserved M. bovis GAPDH was suggested as a potential antigen for diagnosis or vaccines; however, a subunit vaccine based on GAPDH did not protect against M. bovis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the lack of recognition of the M. agalactiae P48 protein by the mAb 10E in Western blot assays and the failure to inhibit binding of the mAb 10E to M. bovis P48 by a rabbit polyclonal antibody against the M. agalactiae P48 protein, the authors concluded that this mAb 10E may be useful in a diagnostic test. Another protein proposed as diagnostic marker for M. bovis infection is the E1 b-subunit of the pyruvate dehydrogenase complex [51].…”
Section: Protein Vaccine Candidatesmentioning
confidence: 99%